2008
DOI: 10.1080/00223890802388624
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Generalization Study of Coefficient Alpha for the UCLA Loneliness Scale

Abstract: Loneliness is a psychological construct that has been reported in a variety of populations and associated with a number of other negative psychological problems. This study was an examination of coefficient alpha of a prominent measure of loneliness: the University of California, Los Angeles (UCLA) Loneliness Scale (Russell, Peplau, & Cutrona, 1980; Russell, 1996). We utilized reliability generalization to provide an aggregate estimate of the reliability of the scale over time and in a variety of populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 83 publications
9
41
0
Order By: Relevance
“…Perhaps a LOT adapted for adolescents with more age appropriate content is warranted. This finding has been observed in other RG studies (Vassar, 2008;Vassar & Crosby, 2008), which may suggest less consistent response patterns among adolescents on self-report instruments. Interestingly, the mean alpha coefficient for adolescents was .61, whereas the nonadolescent mean alpha was .74.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Perhaps a LOT adapted for adolescents with more age appropriate content is warranted. This finding has been observed in other RG studies (Vassar, 2008;Vassar & Crosby, 2008), which may suggest less consistent response patterns among adolescents on self-report instruments. Interestingly, the mean alpha coefficient for adolescents was .61, whereas the nonadolescent mean alpha was .74.…”
Section: Discussionsupporting
confidence: 44%
“…Across analyses, we found that alpha was related to standard deviation, language, and adolescence. Vassar and Crosby's (2008) RG study of the University of California Los Angeles Loneliness Scale (Russell, Peplau, & Cutrona, 1980), also found that standard deviation was related to internal consistency estimates, which is consistent with the formulaic characteristics of coefficient alpha. Vassar and Crosby discussed this matter in greater detail.…”
Section: Discussionmentioning
confidence: 52%
“…It is important to realize that the results of the present article, while encouraging, are dependent on a set of basic assumptions in (Vassar & Crosby, 2008). To the extent that the value used represents an overestimate, the expected degree of attenuation may be less pronounced than assumed in the present analyses.…”
Section: Limitations Of the Present Studymentioning
confidence: 78%
“…The eight item version used required participants to make ratings on a four-point scale, with the anchors 1 (Never) to 4 (Often). UCLA Loneliness scale has demonstrated adequate reliability across samples and is commonly related to numerous indicators of psychological distress (e.g., depression, low selfesteem; see Vassar & Crosby, 2008). The Cronbach alpha in this study was .84.…”
Section: Lonelinessmentioning
confidence: 89%